UJI EFEKTIVITAS EKSTRAK ETANOL DAUN KUNYIT (Curcuma longa LINN.) SEBAGAI ANTIFUNGI TERHADAP PERTUMBUHAN JAMUR Trichophyton rubrum SECARA IN VITRO - Mustofa Lukman Sungkar (2023)
Trichophyton rubrum is a type of dermatophyte fungus with the highest number of cases in Indonesia. A solution is needed to overcome this problem. This research highlights the antifungal properties of turmeric leaf extract (Curcuma longa Linn.), which shows its potential as a treatment for dermatophyte skin infections. This research aims to determine the effectiveness of turmeric leaf ethanol extract as an antifungal against the growth of Trichophyton rubrum in vitro. This research uses an experimental method with a post-test-only control group design in the laboratory. Turmeric leaf extract concentrations of 10%, 20%, 30%, and 40% were tested, along with negative and positive controls (distilled water and ketoconazole, respectively). The diameter of the growth inhibition zone of Trichophyton rubrum on Sabouraud Dextrose Agar media was observed using the well method. The research data were tested using the Kruskal-Wallis test, obtaining P < 0.05 and followed by the Post Hoc Mann Whitney test. The results showed the inhibitory potential of turmeric leaf extract on fungal growth, with the size of the inhibition zone for 10% concentration of 1.2825 mm, 20% concentration of 2.1875 mm, 30% concentration of 3.2875 mm, 40% concentration of 8.3625 mm. Varying results are influenced by extract concentration and incubation time. The most effective concentration was 40%, with a medium-sized inhibition zone diameter of 8.3625 mm at 24 hours and 7.84 mm at 48 hours. This result is due to the presence of compounds such as alkaloids, flavonoids, saponins, tannins, phenols and triterpenoids contained in turmeric leaf extract.